Entrepreneurship Ethics - Syafri Fadillah Marpaung; Ahmad Rifai; Lia Sumayyah; Rani Zaskia Ariesky (Universitas Muhammadiyah Enrekang, 2023)
The purpose of this research is to find out about how people behave as entrepreneurs in their business, known as entrepreneurial ethics. Many business owners overlook the importance of ethics when starting a company because they believe it can be done quickly with a lot of skill and funding. This research uses a qualitative approach, using data processing techniques based on interviews, observations and documentation related to this research. The research results obtained are that in their daily entrepreneurial actions, managers are always faced with ethical dilemmas, which they must maintain continuously because a company's ethical reputation takes time to develop. And goodwill is an invaluable asset for a business.